Miquelianin inhibits IAV infection via the MAPK signaling pathway both in vitro and in vivo - Li, He; Shen, Beilei; Bi, Yan; Sun, Yan; Zhang, Shijun; Xue, Kun; Wang, Qiuyue; Qian, Bingshuo; Zhang, Junkui; Fan, Lingjun; Fang, Zhengyuan; Wang, Tiecheng; et al. (Frontiers in Immunology, 2025)
BackgroundInfluenza is an acute respiratory infectious disease primarily transmitted through airborne droplets. The prevalence and spread of influenza viruses have significant impacts on global economic development and public health. Current prevention and control strategies for influenza virus infections mainly rely on vaccines and antiviral drugs. However, vaccine efficacy is limited by the antigenic drift and mutation characteristics of influenza viruses, while antiviral drug resistance is increasingly prevalent. Therefore, there is an urgent need for the development of novel antiviral agents. Flavonoids, widely distributed in plants, possess various potent biological properties, including antioxidant, anti-inflammatory, antibacterial, and anticancer activities, which contribute to the management and prevention of numerous diseases. This study aims to investigate the in vitro and in vivo anti-influenza A virus activity of quercetin, taxifolin, and miquelianin, as well as their underlying.MethodsIn vitro infection model (MDCK cells) and mouse lethal infection model of Infuenza A virus were used to evaluate the antiviral activity of quercetin, taxifolin and miquelianin. Subsequently, we applied network pharmacology to elucidate the mechanism of action and validate the findings for miquelianin.ResultsMiquelianin effectively inhibits the replication of H1N1-UI182 both in vitro and in vivo and provides protection against lethal H1N1-UI182 infection in mice. Compared to virus-infected controls, miquelianin reduces lung injury. Furthermore, by inhibiting the MAPK signaling pathway, miquelianin prevents the overproduction of cytokines, such as IL-6 and IL-1β, induced by viral infection, thereby alleviating inflammatory responses.ConclusionMiquelianin is a monomer extracted from traditional Chinese medicine, exhibiting inhibitory effects on H1N1-UI182 replication and lung injury mitigation.